2016
DOI: 10.5216/rpt.v45i2.41778
|View full text |Cite
|
Sign up to set email alerts
|

Diversidade, Prevalência E Infecção Natural Por Tripanossomatídeos Em Triatomíneos (Hemiptera: Reduviidae) Do Curimataú E Seridó Paraibanos

Abstract: Os triatomíneos (Hemiptera: Reduviidae) são insetos hematófagos vetores do Trypanosoma cruzi, agente etiológico da doença de Chagas humana. Neste trabalho, objetivou-se avaliar a fauna de triatomíneos capturados em municípios da região do Curimataú e Seridó paraibanos, durante a Campanha do Programa de Controle da Doença de Chagas (PCDCh) em 2013, e fazer um levantamento retrospectivo das espécies capturadas entre 2008 e 2012 na mesma região. Foram realizadas coleta, identificação taxonômica e análise parasito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…brasiliensis and T . pseudomaculata are the most captured species in housing units (HU, including both intra- and peridomestic locations) in the states of Ceará [ 13 – 15 ], Paraíba [ 16 , 17 ], Pernambuco [ 18 ], Bahia [ 19 ] and Rio Grande do Norte [ 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…brasiliensis and T . pseudomaculata are the most captured species in housing units (HU, including both intra- and peridomestic locations) in the states of Ceará [ 13 – 15 ], Paraíba [ 16 , 17 ], Pernambuco [ 18 ], Bahia [ 19 ] and Rio Grande do Norte [ 16 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The northeast region of Brazil has a wide distribution of native species of triatomines, such as T. brasiliensis, T. pseudomaculata and Rhodnius nasutus Stål, 1859 [11,12], with different rates of natural infection by T. cruzi. Several studies have reported that T. brasiliensis and T. pseudomaculata are the most captured species in housing units (HU, including both intra-and peridomestic locations) in the states of Ceara ´[13-15], Paraı ´ba [16,17], Pernambuco [18], Bahia [19] and Rio Grande do Norte [16,20,21].…”
Section: Introductionmentioning
confidence: 99%